The Changes in Biochemical Compositions of Five Different Macroalgae and Seagrass (Halophila stipulacea (Forsskal) Ascherson 1867) Collected from Iskenderun Bay - Eyüp İlker Saygılı; Zafer Çetin; Mehmet Naz; Oktay Söyler; Ergün Taşkın; Selin Sayın (Journal of Advanced Research in Natural and Applied Sciences)
In present study, biochemical compositions (ash, lipid and protein) of five different macroalgae ((Green Macroalgae-GMA (Chaetomorpha linum and Caulerpa prolifera), Red Macroalgae-RMA (Pterocladiella capi-lacea), Brown Macroalgae-BMA (Sargassum vulgare and Ericaria amentacea)) and Angiosperm/Seagrass (Hal-ophila stipulacea) collected from Iskenderun Bay were investigated. The differences observed between biochemical compositions such as ash, lipid and protein of five macroalgae species and Angiosperm/Seagrass (Halophila stip-ulacea) were statistically significant (p<0.05). The lowest and highest ash, lipid and protein values of five macroalgae were 12.19±1.15% (Caulerpa prolifera)- 21.38±1.53% (Ericaria amentacea), 1.74±0.19% (Caulerpa prolifera)- 5.83±0.68% (Ericaria amentacea), 5.56±0.06% (Chaetomorpha linum)- 11.45±0.53% (Sargassum vulgare), respec-tively. Ash, lipid and protein values of Angiosperms/Seagrass (Halophila stipulacea) were determined as 14.56±2.08%, 3.16±0.48% and 8.11±0.07%, respectively. Protein value of Angiosperms/Seagrass (Halophila stipulacea) was higher than those of (GMA (Chaetomorpha linum and Caulerpa prolifera) but not RMA(Pterocladiella capillacea) and BMA (Sargassum vulgare and Ericaria amentacea)). Lipid value of Angio-sperms/Seagrass (Halophila stipulacea) was similar to RMA(Pterocladiella capillacea). In conclusion, the information of the biochemical compositions of five different macroalgae and Angiosperms/Seagrass (Halophila stipulacea) are important for the evaluation of potential sources for commercial and human consumption. In addition, biochemical compositions of tested macroalgae and seagrass could make important contributions to feed formulations and functional foods in future.